2015
DOI: 10.1080/21620555.2015.1096193
|View full text |Cite
|
Sign up to set email alerts
|

Family Background, Private Tutoring, and Children’s Educational Performance in Contemporary China

Abstract: The prevalence of private tutoring is often noted in the literature on education in East Asia. Empirical evidence concerning the causes and consequences of private tutoring, however, is sparse, especially for China. In this article, we draw upon data from the 2010 China Family Panel Studies to explore whether children’s tutoring experiences are influenced by family background and whether private tutoring benefits children’s educational performance. Our empirical analyses show that higher parental education, hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
49
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(50 citation statements)
references
References 40 publications
1
49
0
Order By: Relevance
“…A family's economic condition determines how much parents can invest in their children's education and development (Becker, 1991;Blau, 1999;Brooks-Gunn and Duncan, 1997;Coleman, 1988;Dahl and Lochner, 2012;Duncan et al, 1994;Duncan et al, 1998;Kaushal et al, 2011). Families with higher levels of income can provide material advantages, such as more learning opportunities and resources, that is, high-quality private tutoring (Zhang and Xie, 2015). Another perspective emphasizes families' non-monetary resources, such as parenting attitudes and practices, and family environments (Alexander et al, 1994;Baharudin and Luster, 1998;Cheadle and Amato, 2011;Chen et al, 2000;Davidov and Grusec, 2006;Davis-Kean, 2005;Garrett et al, 1994;Heckman, 2006;Lareau, 2011;Mayer, 1997).…”
Section: Theoretical Motivation and Research Model Family Background mentioning
confidence: 99%
“…A family's economic condition determines how much parents can invest in their children's education and development (Becker, 1991;Blau, 1999;Brooks-Gunn and Duncan, 1997;Coleman, 1988;Dahl and Lochner, 2012;Duncan et al, 1994;Duncan et al, 1998;Kaushal et al, 2011). Families with higher levels of income can provide material advantages, such as more learning opportunities and resources, that is, high-quality private tutoring (Zhang and Xie, 2015). Another perspective emphasizes families' non-monetary resources, such as parenting attitudes and practices, and family environments (Alexander et al, 1994;Baharudin and Luster, 1998;Cheadle and Amato, 2011;Chen et al, 2000;Davidov and Grusec, 2006;Davis-Kean, 2005;Garrett et al, 1994;Heckman, 2006;Lareau, 2011;Mayer, 1997).…”
Section: Theoretical Motivation and Research Model Family Background mentioning
confidence: 99%
“…Ha and Harpham [20] have found that private tutoring does increase the reading ability although it does not have an impact on the writing and numeracy skills of the grade 8 students of Vietnam. Further, Zhang [14], has observed on the effects of private tutoring and identified it has mixed effects on mathematical, Chinese language and English language in China (also in [21]).…”
Section: Literature On Impact Of Private Tutoringmentioning
confidence: 99%
“…Individual level variables related to PT are considered as follows; PT participation (as dummy assigning value 1 if participant), the private tuition expenditure incurred by the household (sum of tuition fee and all other related expenses) [17], number of private tuition classes per week, average private tutoring hours a student take per week. Except the student demography details such as gender, age, socio-economic status of family which comprise of household expenditure, father's and mother's education level and the employment status [1,17,20] were taken as the main controlling factors. Further, this study considered the number of siblings as an explanatory variable [1,2,11,28] because of its spillover effects.…”
Section: Data and Variablesmentioning
confidence: 99%
“…Following this line, many studies find shadow education to be positively correlated with children's educational success (e.g., Dumais ; Kaufman and Gabler ). In light of the previous literatures on shadow education in East Asia (e.g., Bray et al ; Kuan ; Stevenson and Baker ; Zhang and Xie ), we in our supplementary analysis examine whether or not shadow education during senior high school mediates between family background and choice of college study fields. There could be various types of shadow education and we here focus on the one that has been frequently studied in the previous literature, that is, outside‐school tutoring.…”
Section: Resultsmentioning
confidence: 99%